Plasmodium ovale infection in Malaysia: first imported case - Lim, Yvonne Ai Lian; Mahmud, Rohela; Chew, Ching Hoong; Thiruventhiran, T.; Chua, Kek Heng (BioMed Central, 2010)
Background Plasmodium ovale infection is rarely reported in Malaysia. This is the first imported case of P. ovale infection in Malaysia which was initially misdiagnosed as Plasmodium vivax.